Conceptual Framework and Advances in CRISPR-Cas Based and BRED Phage Engineering - Sharma, Riya Manas (International Journal of Scientific Research in Biological Sciences, 2021)
The increased proliferation of multi-antibiotic resistant bacterial pathogens necessitates the development of alternate and supportive therapies to antibiotics. Being natural predators of bacteria, bacteriophages have garnered recent attention for their untapped potential to mitigate the public health problem. Progress in synthetic biology has led to the genetic engineering of phages to ameliorate their efficacy and precision via methods such as genome editing, modification of tail fibers, and treatment with chemical mutagens. This review will elucidate two promising genetic engineering strategies, CRISPR-Cas and Bacteriophage Recombineering of Electroporated DNA (BRED), as well as the advances and potential future developments in the field.